2006
DOI: 10.1200/jco.2005.03.7259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Affect the Impact of an Uninformative DNA Test Result: The Course of Worry and Distress Experienced by Women Who Apply for Genetic Testing for Breast Cancer

Abstract: Women with an uninformative result form a heterogeneous group of test applicants. The subpopulation of those with both a personal history of cancer and a relatively high pedigree-based risk expressed the highest levels of worry 7 months after DNA testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 18 publications
(8 reference statements)
8
81
2
3
Order By: Relevance
“…In fact, distress levels decreased from before to after testing more among individuals for whom reducing uncertainty was an important motive for wanting a predictive HNPCC test [30]. Furthermore, uninformative results in genetic testing for breast and ovarian cancer genes resulted in higher anxiety and depression than positive results [31], and in less reassurance than negative results [32]. In our study, we expected mutation status (unequivocal positive and negative results and indeterminate results) to effect reactions to HNPCC testing above and beyond personal cancer history.…”
Section: Introduction and Aimmentioning
confidence: 99%
“…In fact, distress levels decreased from before to after testing more among individuals for whom reducing uncertainty was an important motive for wanting a predictive HNPCC test [30]. Furthermore, uninformative results in genetic testing for breast and ovarian cancer genes resulted in higher anxiety and depression than positive results [31], and in less reassurance than negative results [32]. In our study, we expected mutation status (unequivocal positive and negative results and indeterminate results) to effect reactions to HNPCC testing above and beyond personal cancer history.…”
Section: Introduction and Aimmentioning
confidence: 99%
“…about psychological distress. Mean age and mean education level seem to be a little higher than in previous studies in our center [21]. We have addressed these limitations in an ongoing nationwide prospective and retrospective study with control groups, validated measures and the inclusion of relatives.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…exclusion of a known familial mutation), but less distress than those who received a certain positive result (a pathogenic mutation) [17][18][19][20][21]. In two studies, uncertain positive results (UV) did not seem to cause more psychological distress than a certain DNA result [22,23].…”
Section: The Genetic-uncertainty-causes-distress Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The larger percentage of unaffected counselees in the WM did thus not explain the higher worry of WM counselees. Indeed, studies within Dutch centres reported similar pre-visit cancer worry and knowledge for affected and unaffected counselees (Van Dijk et al 2006;Pieterse et al 2011). Importantly, a comparative study of UK cancer genetic centres found no significant differences in counselees' cancer worry between centres pre-counselling (Hopwood et al 2004).…”
Section: Discussionmentioning
confidence: 94%